The water quality parameters controlling diatoms assemblage in Rawapening Lake, Indonesia - T. R. SOEPROBOWATI; S. D. TANDJUNG; SUTIKNO SUTIKNO; S. HADISUSANTO; P. GELL; HADIYANTO HADIYANTO; S. W.A. SUEDY (Society for Indonesian Biodiversity, 2016)
Soeprobowati TR, Tandjung SD, Sutikno, Hadisusanto S, Gell P, Hadiyanto. 2016. The water quality parameters controlling diatoms assemblage in Rawapening Lake, Indonesia. Biodiversitas 17: 657-664. Diatoms are microalgae that have an important role in aquatic ecosystem. The silicious diatoms fossil had been used for paleolimnological analysis. However, data set diatoms of Indonesia does not develop yet. The aims of this research were to assess water quality parameters controlling diatoms assemblage of RawapeningLake, to assess transfer function, to develop diatoms data set of Rawapening, and to compare Rawapening diatoms data set with European diatoms data set for the reconstruction of total phosphorous and pH. Water samples were taken from 3 sites of Rawapening Lake for water quality analysis. Sediment samples had been taken from 3 sites in Rawapening Lake using hand auger, and were sliced every 0.5 cm for diatoms analysis. Diatoms slides were prepared from about 5 g of dry sediment using 10% of chloride acid followed by 10% of peroxide to remove organic matters and carbonates, respectively.300 diatom valves were calculated on the entire samples, calculation the number of valve’s diatom aims to identify the lowest level of taxonomy. Phosphate, temperature, and calcium were theenvironmental parameters that influence the diatoms assemblage of Rawapening Lake. Phosphate was contributed 50% on diatoms assemblage. Internal based transfer function of diatoms provides more suitable diatoms data set rather than European diatom data set. The Rawapening diatoms data set of total phosphorous is the initial Indonesian diatoms data set for past trophic status, therefore, research has to be continued spatially for other Indonesian lakes and temporary on specific Indonesian lake to develop Indonesia diatoms data set.